Influence of demographic and individual difference factors on impulse buying - Mirela Mihić; Ivana Kursan (Tržište, 2010)
The main purpose of the paper is to determine the correlation of consumers’ demographic or socioeconomic characteristics and individual difference factors on the impulse buying behavior with respect to a number of single impulsivity indicators and one collective indicator. The paper consists of theoretical and research aspects. The first part encompasses theoretical insights into the secondary research regarding impulse buying while the practical part presents the methodology and primary research results. With respect to the subject matter, research goals as well as previous findings and primary research results, corresponding hypotheses were set and mainly confirmed. The results showed that demographic factors, such as the age and working status, are related to most impulse buying indicators and to the impulsivity collective indicator. However, household income produced opposite results. Household income proved to have no major influence on the majority of impulse buying indicators but to be related noticeably to the collective impulsivity indicator, indicating that this result should be regarded with caution. Research results also pointed to the fact that the majority of individual indicators (innovativeness, tendency to the fashionable and shopping enjoyment) are positively and negatively related to the impulse buying behavior and that individual difference factors have a greater influence on impulse buying than do demographic characteristics. The paper also summarizes research limitations as well as the work contribution and future research guidelines.